Immobilization by adsorption of hydrophobic lipase derivatives to porous polymer beads for use in ester synthesis - Ampon, K.; Basri, M.; Salleh, A.B.; Wan Yunus, W.M.Z.; Razak, A.C.N. (Informa Healthcare, 1994)
A novel procedure for attaching lipase to certain kinds of hydrophobic surfaces is described. The procedure involves covalent derivatization of the protein molecule by reaction in solution with a hydrophobic imidoester, aldehyde or activated polyethylene glycol. The resulting protein derivative is then allowed to adsorb onto an insoluble hydrophobic surface. Quantitative adsorption is observed and the enzyme is bound very strongly on the support The number and nature of the hydrophobic substituents introduced in the chemical derivatization step can be easily controlled. The adsorption step occurs spontaneously upon exposure of the modified protein to a variety of hydrophobic materials. The hydrophobic lipase derivative obtained by reaction with PEG activated with p-nirrophenyl chloroformate, for example, adsorbs readily onto polyacrylate and polystyrene beads, with most of its esterification activity in organic solvent intact. Its thermostability is also greatly enhanced. Derivatization of lipase with hydrophobic groups greatly enhances its esterification activity in organic solvent, and its immobilization in this manner enables the preparation of a highly reactive biocatalyst for biotechnological application.